Synergistic anti-oral cancer effects of UVC and methanolic extracts of Cryptocarya concinna roots via apoptosis, oxidative stress and DNA damage. (3rd May 2016) - Chang, Hsueh-Wei; Tang, Jen-Yang; Yen, Ching-Yu; Chang, Hsun-Shuo; Huang, Hurng-Wern; Chung, Yi-An; Chen, Ih-Sheng; Huang, Ming-Yii
Abstract: Purpose Radiation combined with natural products may improve the radiosensitivity of cancer cells. This study investigated the potential of a combined modality treatment with Ultraviolet C (UVC; wavelength range 200–280 nm) and our previously identified anti-oral cancer agent (methanolic extracts of Cryptocarya concinna roots; MECCrt) in oral cancer cells. Materials and methods The mechanism of the possible synergy of UVC and MECCrt was explored in terms of cell viability, cell cycle, apoptosis, reactive oxygen species (ROS), mitochondrial membrane potential (MitoMP), and DNA damage analyses. Results In cell viability (%) at 24 h treatment, the low doses of UVC (14 J/m 2 ) and MECCrt (10 μ g/ml) resulted in slight damage to human oral cancer Ca9-22 cells (83.2 and 80.4) but was less harmful to human oral normal HGF-1 cells (93.4 and 91.8, respectively). The combined treatment of UVC and MECCrt (UVC/MECCrt) had a lower viability (54.5%) than UVC or MECCrt alone in Ca9-22 cells but no showed significant change in HGF-1 cells. In Ca9-22 cells, the expression of flow cytometry-based apoptosis (sub-G1 phase, annexin V, and pancaspase assays) was significantly higher in UVC/MECCrt than in UVC or MECCrt alone ( p < 0.0001). Using flow cytometry, intracellular ROS levels of UVC/MECCrt and MECCrt alone were higher than for UVC alone. MitoMP change and H2A histone family member X (γH2AX; H2AFX)-based DNA damage were synergistically inhibited and induced by MECCrt/UVC compared to its single treatment in Ca9-22 cells, respectively. Conclusion UVC plus MECCrt treatment had selective killing and synergistic anti-proliferative effects against oral cancer cells involving apoptosis, oxidative stress, and DNA damage. This combination therapy appears to have a great clinical potential against oral cancer cells.